The Effect of Ozonation Technique and Treatment Duration on The Freshness of Horticultural Product Chili (Capsicum annum L.) - Indriati Meilina Sari; Andika Prawanto; Kiky Nurfitri Sari; Paisal Ansiska (University of Prof. Dr. Hazairin, SH, 2023)
Chili is a perennial plant of the Capsicum genus that can grow in both highland and lowland areas. It has a spicy taste due to the presence of capsaicin. The damage to chili products can be classified into mechanical and pathological damage. Steps used to minimize pathological damage include using irradiation and plasma techniques. Irradiation and plasma technologies can be applied by utilizing ozone on horticultural products. This research aims to determine the influence of ozone technique and treatment duration to preserve the freshness of chili horticultural products. The experimental design used in this research is a Randomized Complete Block Design with the treatment factors of ozone technique and treatment duration. The variables in this study include weight loss, changes in vitamin C content, texture, color, and aroma of chili. Ozone technique with ozone gas flow and a treatment duration of 30 minutes yielded the best results for all research variables.